Gambaran Konsep Diri Pasien Kanker Payudara di Poliklinik Bedah RSUD Dr. M. Djamil Padang Tahun 2013 : Self-Concept of Breast Cancer Patients in the Surgical Polyclinic of RSUD Dr. M. Djamil Padang in 2013 - Yulastri; Aini Yusra; Novi Herawati (NERS Jurnal Keperawatan, 2016)
Breast cancer cause various psychological symptoms as a result of changes in body shape, uncertainty about the future, and the impact of recurrence of breast cancer treatment. As a result, many patients don’t adhere to treatment. Negative self-concept is a response that is maladaptive adjustment. According to WHO the incidence increased every year, 6.25 million people in 2002. The aim of research to describe the concept of self-breast cancer patients at the Clinic Surgical Hospital Dr M Djamil Padang 2013. This research is descriptive, at the Polyclinic Hospital Surgery Dr. M Djamil Padang. Population is all of breast cancer patients who visited the Polyclinic Surgery amounted to 234 people. Accidental sampling as many as 49 people. Data were collected in July 2013 using a questionnaire and analyzed by univariate. Results of the study the majority (57.1%) of respondents have a positive body image. Most (57.1%) of respondents have a negative self ideal. General (75.5%) of respondents have a negative self-esteem. Most (53.1%) of respondents have a negative self-identity and most (51%) of respondents have a negative self role. Surgery Clinic nurses are expected to be able to conduct assessments of physiological stressors, self-concept in patients with breast cancer by providing health education and motivate patients to seek treatment until complete. As well as the need for cognitive therapy given by a nurse specialist mental patients with breast cancer to improve their quality of life.